Iron Age Blacksmithing Site Identification Issues in Lithuanian Archaeology - Bodrijė, Matas (Archaeologia Lituana, 2025)
The article examines the problems of identifying Iron Age blacksmithing sites in Lithuania – a field that has so far remained little studied, and its research was usually based on fragmentary data or imprecise interpretations. The main directions of iron archaeometallurgical research are analysed, alongside the issue of the term ‘blacksmithing slag’ and proposed terminological adjustments. The study presents the macro- and micro-level features of blacksmithing activity and guidelines for their recognition. Particular attention is given to the analysis of hammerscale, whose international research has demonstrated to be the most reliable indicator of long-term smithing. The principles of initial recognition, systematic sampling, laboratory analyses, and the potential of additional methods are discussed. Based on foreign experience, recommendations are formulated on how these approaches could be applied in Lithuanian archaeology, in order to move from the currently established fragmentary practices towards complex research grounded in new data. The article emphasises that, without a systematic investigation of blacksmithing sites, it is impossible to address fundamental questions about the production scale, technological development, the organisation of the craft, and its contribution to the economy, military capacity, and the formation of social and political structures in Iron Age communities.